Patterns of left ventricular trabeculation in hypertrophic cardiomyopathy - Yu Zhang; Di Zhou; Yuming Zhu; Qiya Huang; Jizheng Wang; Channa Zhang; Lianming Kang; Minjie Lu; Lei Song (BMC Medicine)
Background Left ventricular (LV) trabeculation are increasingly observed in patients with hypertrophic cardiomyopathy (HCM), but its clinical significance remains controversial. This study aims to clarify the characteristics of LV trabeculation and evaluate its prognostic value in HCM. Methods We evaluated 1028 patients with HCM undergoing cardiac magnetic resonance. For each patient, thickness of compacted and trabeculated myocardium was measured at 16 segments of LV. The extent of LV trabeculation was expressed as the maximal trabeculation/compaction (T/C) ratio in any of 16 segments. The primary endpoint was major adverse cardiovascular events (MACEs). The secondary endpoints were heart failure, thromboembolic events, and ventricular arrhythmias. There were 689 patients undergoing whole-exome sequencing. Results LV trabeculation predominantly located in midventricular-to-apical area, anterior, and lateral free walls in HCM. A greater extent of LV trabeculation was correlated with a higher prevalence of female, lower LV ejection fraction, and higher prevalence of extensive late gadolinium enhancement. During a median 4.8-year follow-up, a greater extent of LV trabeculation was associated with an increased risk of MACEs (adjusted hazard ratio [HR] 1.214, P = 0.005), heart failure (adjusted HR 1.372, P = 0.006), thromboembolic events (adjusted HR 1.242, P = 0.032), and ventricular arrhythmias (adjusted HR 1.240, P = 0.047). No gene was significantly associated with trabeculation at genome-wide level. Conclusions The distribution pattern of LV trabeculation was inhomogeneous and asymmetric in HCM. A greater extent of LV trabeculation was associated with poor prognosis. The progression of LV trabeculation might be the natural course of HCM. Graphical Abstract The distribution pattern of LV trabeculation in patients with HCM and the association between the extent of LV trabeculation and poor prognosis. CMR, cardiac magnetic resonance; HCM, hypertrophic cardiomyopathy; MACEs, major adverse cardiovascular events; LGE, late gadolinium enhancement; LV, left ventricular; LVEF, LV ejection fraction; WES, whole-exome sequencing